2005
DOI: 10.1021/la0504210
|View full text |Cite
|
Sign up to set email alerts
|

Metal Speciation Dynamics in Colloidal Ligand Dispersions

Abstract: In this work we propose a dynamic metal speciation theory for colloidal systems in which the complexing ligands are localized on the surface of the particles; i.e., there is spatial heterogeneity of binding sites within the sample volume. The differences between the complex formation and dissociation rate constants of complexes in colloidal dispersions and those in homogeneous solutions originate from the differences in kinetic and mass transport conditions. In colloidal systems, when the effective rate of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
116
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(129 citation statements)
references
References 26 publications
10
116
0
3
Order By: Relevance
“…This feature has important consequences for the dynamic properties of the metal species. For ligands located on the surface of colloidal particles it has already been shown that the dynamic metal speciation features arise from the coupling between the chemical kinetics of complex formation/dissociation and the local diffusion-controlled transport of metal ions to/from the particle [1]. That led us to introduce the concept of 'generalized' rates of association and dissociation for colloidal metal complexes, k à a and k à d [1], which may differ by several orders of magnitude from their homogeneous solution counterparts, k a and k d .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature has important consequences for the dynamic properties of the metal species. For ligands located on the surface of colloidal particles it has already been shown that the dynamic metal speciation features arise from the coupling between the chemical kinetics of complex formation/dissociation and the local diffusion-controlled transport of metal ions to/from the particle [1]. That led us to introduce the concept of 'generalized' rates of association and dissociation for colloidal metal complexes, k à a and k à d [1], which may differ by several orders of magnitude from their homogeneous solution counterparts, k a and k d .…”
Section: Introductionmentioning
confidence: 99%
“…For ligands located on the surface of colloidal particles it has already been shown that the dynamic metal speciation features arise from the coupling between the chemical kinetics of complex formation/dissociation and the local diffusion-controlled transport of metal ions to/from the particle [1]. That led us to introduce the concept of 'generalized' rates of association and dissociation for colloidal metal complexes, k à a and k à d [1], which may differ by several orders of magnitude from their homogeneous solution counterparts, k a and k d . The conventional approach of taking a colloidal ligand dispersion as a smeared-out homogeneous solution [2][3][4] overestimates both the dynamics and the lability of the colloidal metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…14 The basic Eigen mechanism was kept virtually unchanged in the electroanalytical field since the introduction of the first lability criteria 15 (Figure 2) until 2005. 16 With the advent of the stripping chronopotentiometry in the early 2000s, and especially the scanned deposition potential mode in 2003, the direct determination of the kinetic parameters using that technique clearly showed that the basic Eigen mechanism could not explain more involved systems like the metal ion complexation in colloidal systems and/or with multidentate ligands.…”
Section: Dynamic Speciation By Electrochemicalmentioning
confidence: 99%
“…Pinheiro et al 16 pointed out that, in colloidal systems, the ligands are localized within the vicinity of the particles, whereas in true solutions the ligand distribution is taken as homogeneous over the solution volume (Figure 3). In this case the local diffusion-controlled transport of metal ions to/ from the particle must be taken into account.…”
Section: Dynamic Speciation By Electrochemicalmentioning
confidence: 99%
See 1 more Smart Citation